Crystal structure of chlorido-(O-methyl phenylcarbamothioamide-κS)-bis(triphenylphosphane-κP)silver(I), C44H39AgClNOP2S - Yeo, Chien Ing *; Teow, Sin Yeang *; Liew, Li Yuan *; Chew, Jactty *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C44H39AgClNOP2S, triclinic, P1̄ (no. 2), a = 10.2520(3) Å, b = 13.2252(4) Å, c = 14.9378(3) Å, α = 78.424(2)°, β = 78.388(2)°, γ = 84.534(3)°, V = 1940.35(9) Å3, Z = 2, Rgt(F) = 0.0382, wRref(F2) = 0.0807, T = 100(2) K.